Pseudomonas aeruginosa as an uncommon agent of infectious panniculitis - Tatiana Mina Yendo; Cristina de Castro Pante; Denise Miyamoto (Sociedade Brasileira de Dermatologia, 2022)
Abstract Pseudomonas aeruginosa is a Gram-negative bacillus that frequently causes septicemia, abscesses and infections in skin wounds. Panniculitis caused by this microorganism is unusual and there are few well-documented cases, none of them in a patient with systemic lupus erythematosus. The present report describes an immunosuppressed patient with systemic lupus erythematosus who developed panniculitis caused by Pseudomonas aeruginosa, with a review of the literature on this rare presentation.